Analisis Perbandingan Efektifitas White-Box Testing dan Black-Box Testing - Dede Wintana; Denny Pribadi; Moh Yusup Nurhadi (LPPM Universitas Bina Sarana Informatika, 2022)
This research, will descibe about comparison of black-box testing with manual testing. Researcher will compare how efficient is white-box testing and manual testing. In usage which one is better and which one is worse. This research will compare them by data to show how efficient they ares. The research also show the chart of white-box and manual testing comparison. The complete result will described as journal seen describing below.